Venture capital and internationalization - Andrea Schertler; Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Cross-border investments represent a substantial share of venture capital activities. We use a new and comprehensive dataset on worldwide investments to analyze the internationalization of venture capital financing. Our results from the perspectives of (i) venture capitalists, (ii) portfolio companies, (iii) portfolio companies' countries and (iv) pairs of venture capitalists' and portfolio companies' countries suggest that some factors, such as viable stock markets, boost investments by domestic as well as by foreign venture capitalists. Therefore, our results are of interest not only to academics but also to policy makers who want to foster the growth of the local venture capital industry and local companies.
Keywords: F21; G24; 330; Venture capital; internationalization; macroeconomic factors; Risikokapital; Portfolio-Investition; Institutioneller Anleger; Multinationales Unternehmen; Makroökonomischer Einfluss; Aktienmarkt; Standortfaktor; Welt